2006
DOI: 10.1021/la053071q
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Unique Electron Donor−Acceptor Property for Platinum Nanoparticles as Studied by XPS

Abstract: In the interaction of PVP with Pt nanoparticles <7 nm in size, charge transfer is from carbonyl groups in PVP to Pt nanoparticles, whereas in the interaction of PVP with bulk Pt or Pt nanoparticles >25 nm in size, charge transfer is from Pt metal to the polymer side chain of PVP. There exists a critical nanoparticle size between 7 and 25 nm that would lead to a switch in the electron donor-acceptor property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(166 citation statements)
references
References 14 publications
16
150
0
Order By: Relevance
“…63 Several studies have shown that charge transfer and the co-ordination mode of PVP molecules with noble metal nanoparticles to be size dependent. [64][65][66] The XPS data in this study also indicates that the interaction mode of PVP capping ligands is also dependent on the nature of the surface facet for Pd NCs. This finding is important for both shape selective NC synthesis with high energy faceted surfaces, suggesting that the structure and electronic interaction of the ligand is important in preserving the long term stability and structure of high energy surfaces.…”
Section: Oxidation and Interaction Of Pvp With Pd Nanocrystalsmentioning
confidence: 82%
“…63 Several studies have shown that charge transfer and the co-ordination mode of PVP molecules with noble metal nanoparticles to be size dependent. [64][65][66] The XPS data in this study also indicates that the interaction mode of PVP capping ligands is also dependent on the nature of the surface facet for Pd NCs. This finding is important for both shape selective NC synthesis with high energy faceted surfaces, suggesting that the structure and electronic interaction of the ligand is important in preserving the long term stability and structure of high energy surfaces.…”
Section: Oxidation and Interaction Of Pvp With Pd Nanocrystalsmentioning
confidence: 82%
“…In addition to this, there is an additional peak for unreduced palladium at 343.24 and 337.82 eV corresponding to the 3d3/2 and 3d5/2 levels, respectively. The emergence of new peaks at higher binding energy 29 suggests that there is a charge transfer from the metal-to-polymer matrix. The analysis further reveals that 29.44% of Pd 0 is influenced by the donor-acceptor interaction; 56.40% of Pd 0 is unaffected by this interaction and the remaining 14.16% is unreduced Pd.…”
Section: Resultsmentioning
confidence: 99%
“…In general, PtNPs are prepared via the chemical reduction of Pt 4+ ions by hydrogen [6,9], alcohols [2,5,[10][11][12][13], borohydride [14][15][16][17][18], glycol [3,6], or ethylene glycol [19,20] in the presence of a stabilizer or on a solid support (Scheme 1). Among the aforementioned reducing agents, borohydride (BH 4 -) is most suitable for minimizing the particle size because it enables rapid reduction to afford very small nuclei, whose growth is hindered.…”
Section: Introductionmentioning
confidence: 99%